Designing Cathodes and Cathode Active Materials for Solid‐State Batteries. Issue 35 (28th July 2022) - Minnmann, Philip; Strauss, Florian; Bielefeld, Anja; Ruess, Raffael; Adelhelm, Philipp; Burkhardt, Simon; Dreyer, Sören L.; Trevisanello, Enrico; Ehrenberg, Helmut; Brezesinski, Torsten; Richter, Felix H.; Janek, Jürgen
Abstract: Solid‐state batteries (SSBs) currently attract great attention as a potentially safe electrochemical high‐energy storage concept. However, several issues still prevent SSBs from outperforming today's lithium‐ion batteries based on liquid electrolytes. One major challenge is related to the design of cathode active materials (CAMs) that are compatible with the superionic solid electrolytes (SEs) of interest. This perspective, gives a brief overview of the required properties and possible challenges for inorganic CAMs employed in SSBs, and describes state‐of‐the art solutions. In particular, the issue of tailoring CAMs is structured into challenges arising on the cathode‐, particle‐, and interface‐level, related to microstructural, (chemo‐)mechanical, and (electro‐)chemical interplay of CAMs with SEs, and finally guidelines for future CAM development for SSBs are proposed. Abstract : In this perspective, the required properties and possible challenges for inorganic cathode active materials (CAMs) employed in solid‐state batteries (SSBs) are discussed and design principles are introduced. Solid‐state battery cathode challenges are structured on cathode‐, particle‐, and interface‐level, related to microstructural, (chemo‐)mechanical, and (electro‐)chemical interplay of CAMs with solid electrolytes and guidelines for future CAM development for SSBs are proposed.